Comparison of phase mapping and electrogram‐based driver mapping for catheter ablation in atrial fibrillation. Issue 2 (27th December 2018) - Lin, Chin‐Yu; Lin, Yenn‐Jiang; Narayan, Sanjiv M.; Baykaner, Tina; Lo, Men‐Tzung; Chung, Fa‐Po; Chen, Yun‐Yu; Chang, Shih‐Lin; Lo, Li‐Wei; Hu, Yu‐Feng; Liao, Jo‐Nan; Tuan, Ta‐Chuan; et al.
Abstract: Introduction: Adjunctive driver‐guided ablation in addition to pulmonary vein isolation has been proposed as a strategy to improve procedural success and outcomes for various populations with atrial fibrillation (AF). First, this study aimed to evaluate the different mapping techniques for driver/rotor identification and second to evaluate the benefits of driver/rotor‐guided ablation in patients with paroxysmal and persistent AF (PerAF). Methods: We searched the electronic database in PubMed using the keywords "atrial fibrillation, " "rotor, " "rotational driver, " "atrial fibrillation source, " and "drivers" for both randomized controlled trials and observational controlled trials. Clinical studies reporting efficacy or safety outcomes of driver‐guided ablation for paroxysmal AF or (PerAF) were identified. We performed subgroup analyses comparing different driver mapping methods in patients with PerAF. The odds ratios (ORs) with random effects were analyzed. Results: Out of 175 published articles, seven met the inclusion criteria, of which two were randomized controlled trials, one was quasiexperimental study, and four observational studies (three case‐controlled studies and one cross‐sectional study). Overall, adjunctive driver‐guided ablation was associated with higher rates of acute AF termination (OR: 4.62, 95% confidence interval [CI]: 2.12‐10.08; P  < 0.001), lower recurrence of any atrial arrhythmia (OR: 0.44, 95% CI: 0.30‐0.065; P  < 0.001), and comparable complication incidence. Conclusions: Adjunctive driver‐guided catheter ablation suggested an increased freedom from AF/AT relative to conventional strategies, irrespective of the mapping techniques. Furthermore, phase mapping appears to be superior to electrogram‐based driver mapping in PerAF ablation.